Terapeutas ocupacionais no campo das emergências e desastres, no Brasil - Ribeiro, Fernanda Laís (2025)
Emergencies and disasters are inherently social phenomena. Often approached from the perspective of risk, these situations reveal complex demands, both individual and collective, that directly affect human rights, such as freedom, dignity, and access to justice. Their effects expose issues such as ethical dilemmas, human actions and omissions, economic and political interests, and scientific hesitations and denialism. The choices made to protect lives and contain damage often deepen inequalities, highlighting overlapping vulnerabilities and unequal access to life-saving resources. In Brazil, the COVID-19 pandemic, recurring disasters caused by heavy rains, fires, and the collapse of Vale and Samarco dams have exposed preexisting structural weaknesses in the State and society. This reaffirms the urgency of effective planning, intersectoral actions and actions supported by justice, in which occupational therapists have a relevant role to play, especially in expanding participation, promoting equity and life possibilities in the face of occupational interruption in those affected. Therefore, this study aims to articulate levels of analysis in relation to the possible practices that have been developed by occupational therapists in the field of emergencies and disasters, with the objective of identifying characteristics and priorities, revealing, discussing and improving possible theoretical-practical perspectives currently in use. Therefore, it is about considering how occupational therapists can contribute equally in the field of emergencies and disasters, considering their choices, but also the social, historical, multicultural, ethical and political reality of the Brazilian context. To this end, a single case study was conducted, articulating interviews with twelve occupational therapists who were and/or continue to be involved with the disaster at Boate Kiss, in Rio Grande do Sul, whose findings were worked on based on thematic analysis. The narratives indicate that work in this field remains historically marked by predominantly reactive approaches, strongly influenced by theoretical-practical frameworks and international regulations that do not always reflect local historical, social, and cultural specificities. The participants revealed sensitive and collective practices, reconfiguring notions of justice and public policy, and acting as agents of care and social transformation in the gaps left by ineffective social protection structures. The study contributes to the field by valuing narratives that reveal the profession's ethical, moral, and political commitment, but also exposes persistent gaps in training, formal recognition, and conceptual clarity regarding emergencies and disasters. It is also recognized that the emphasis on reactive actions limits the exploration of dimensions such as prevention and preparedness. Future research is recommended to deepen the understanding of disasters as social phenomena, invest in practical instruction and simulations in training processes, explore the implementation of public policies for the care of frontline professionals while affected, and investigate strategies for transitioning from a reactive logic to proactive approaches.